2009
DOI: 10.2516/ogst/2009004
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of CoMoS and NiMoS Catalysts: from Nano-Crystallite Morphology to Selective Hydrodesulfurization

Abstract: Résumé -Étude DFT des catalyseurs CoMoS et NiMoS : de la morphologie des nano-cristallites à l'hydrodésulfuration sélective -Cet article présente des résultats récents obtenus dans des études utilisant la théorie de la fonctionnelle de la densité (DFT) pour la caractérisation à l'échelle atomique des phases actives Co(Ni)MoS utilisées en catalyse d'hydrodésulfuration (HDS) sélective. L'effet des conditions du milieu réactionnel sulfo-réducteur sur la stabilité et la nature des sites actifs localisés au bord de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 82 publications
1
34
0
Order By: Relevance
“…In both cases, the promoter-to-molybdenum atomic ratios in the nanocrystallites do not exceed 0.5, which is in agreement with nanocrystallites morphologies obtained by DFT [21,22]. The optimum obtained is the same for both promoters.…”
Section: (4)supporting
confidence: 73%
See 2 more Smart Citations
“…In both cases, the promoter-to-molybdenum atomic ratios in the nanocrystallites do not exceed 0.5, which is in agreement with nanocrystallites morphologies obtained by DFT [21,22]. The optimum obtained is the same for both promoters.…”
Section: (4)supporting
confidence: 73%
“…From DFT modeling [21,22], it is known that the NiMoS crystallites exhibit a deformed hexagon-like two-dimensional morphology with a proportion of M-edge of about 0.6-0.65 in HDT conditions (Fig. 8), which provides us with Equation (4).…”
Section: Nimo Vs Como Catalysts: Optimal Morphologies and Edges Decormentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, the Mo-edge structure exhibits mixed Co-Mo sites while the sulfur atom is located at the top of the molybdenum atoms. Nevertheless, it was also found that sulfur atoms might also be located in bridging positions, which indicated that the mobility of sulfur atoms on the Mo-edge is high (Krebs et al, 2009;Schweiger et al, 2002). To illustrate the experimentally observed morphologies, two models for the cobaltmolybdenum-sulfur and cobalt-tungsten-sulfur catalysts were built (see Figures 4.42c and 4.42d).…”
Section: Co-doped Mos 2 /Ws 2 Nanowire Catalystsmentioning
confidence: 99%
“…In the past two decades, numerous configurations for the sulfulradsorption and the cobalt-promoter distribution at the molybdenum and sulfur active edges of MoS 2 have been intensively investigated by different theoretical and experimental groups. One of the most relevant density functional theory simulation results shows that, for typical HDS conditions, the energy of the S-edge with 100% cobalt is lower than the Mo-edge with 100% cobalt (Krebs et al, 2009;Schweiger et al, 2002;Byskov et al, 2000;Sun et al, 2004a). However, in addition to the affinity of cobalt for the S-edge under such reaction conditions, a 50% cobalt-promoter decoration of the Mo-edge reduces considerably the edge energy of the Mo-edge to a value close to the S-edge value.…”
Section: Co-doped Mos 2 /Ws 2 Nanowire Catalystsmentioning
confidence: 99%